الأصول الدينية للمركزية الأوربية عند هيجل - بالضياف خالد (University of Eloued جامعة الوادي, 2024)
نُقارب من خلال هذه الدراسة مسألة المركزية الأوربية عند هيغل، ولما نتكلم عن هيجل فمن الطبيعي أن تتأرجح أغلب الفلسفات المعاصرة في فلكه إما تأييدا أو معارضة، وتكتسب مسألة الدين عند هيجل أهميتها في سياق دراسة الفلسفة الهيغلية عموما، وفي فلسفة الروح على وجه الخصوص، حيث يتبين من خلالها عقدة المركزية الأوربية التي طبعت فلسفته، وجعلته فيلسوف المركزية الأوربية بدون منازع، فتجلت في فلسفته ثنائية الهيمنة والإقصاء التي مارسها الفكر الغربي عموما تجاه الثقافات والأديان الأخرى. وتأتي هذه الدراسة لتسلط الضوء على أحد أهم الأسس التي شكلت التمركز الأوربي عند هيجل وهي الديانة المسيحية، حيث عمل على الإعلاء من شأنها، وفي نفس الوقت الحط من شأن الأديان الأخرى، وبذلك يتبين بأن كل خطاب أو فلسفة أو نظرية في العلوم الإنسانية والاجتماعية تحمل ورائها أيديولوجيا مهما حاولت أن تكون علمية وموضوعية، وهذا ما يتضارب مع مكانة هيجل كفيلسوف عالمي، ويطرح عدة علامات استفهام حول الفلسفة الدائمة التي كان يصبو إليها. Abstract: Through this study we approach the question of Hegel's Eurocentrism, and when we talk about Hegel, it is natural that most contemporary philosophies swing in its orbit, either in support or opposition, and the issue of religion for Hegel acquires its importance in the context of the study of Hegelian philosophy in general, and in the philosophy of soul in particular, where Through it, the European centralism complex that characterized his philosophy, and made him the philosopher of European centralism unchallenged, manifested in his philosophy of the duality of domination and exclusion that Western thought practiced in general towards other cultures and religions. This study comes to shed light on one of the most important foundations that formed the European concentration at Hegel, which is the Christian religion, as he worked to uphold it and at the same time demean other religions, and thus it becomes clear that every discourse, philosophy or theory in the human and social sciences carries behind it. Ideology, no matter how scientific and objective it tries to be scientific and objective, and this is inconsistent with Hegel's position as a world philosopher, and raises several question marks about the permanent philosophy that he was aiming for
Keywords: مركزية; أوربا; أديان; مسيحية; مُطلق; Centralized; Europe; HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology, North European; Christian; Absolute